Erratum to “Feller Semigroups Obtained by Variable Order Subordination" (Rev. Mat. Complut. 20 (2007), no. 2, 293-307) - Evans, Kristian P.; Jacob, Niels (Revista Matemática Complutense, 2009)
Sin resumen